Evaluation of students’Knowledge, Attitude and Practice in Relation to Preventive Strategies against Leishmaniasis in the Hyperendemic Region of Shahid Babaie Airbase - Sedighe Saberi; Ahmad Reza Zamani; Neda Moatamedi; Mohammad Ail Nilforoushzadeh; Fariba Jaffary; Ezatolah Rahimi; Seyed Hossein Hejezi (مجله دانشکده پزشکی اصفهان, 2012)
Background: Shahid Babaie airbase is one of the most important centers of leishmaniasis in Isfahan province. It has been suggested that the training of high risk communities about preventive methods is one of the most effective strategies against leishmaniasis. Regarding the higher incidence rates of the disease among the youth and their sensitivity to the infection, we decided to examine the knowledge, attitude and practice of guidance and high school students in relation to preventive strategies in that region. We also aim to provide training programs to improve preventive behaviors against leishmaniasis in the next phase of the project. Methods: The target population of this cross-sectional study was the students of guidance and high schools in Shahid Babaie Airbase region of Isfahan. Sampling was done by consensus method. The questionnaires consisted of items about knowledge, attitude and practice which were categorized into 3 grades (weak, intermediate and strong) on the basis of collected scores. The questionnaires were filled out during personal interviews. Findings: From 450 subjects enrolled, 245 were high school (126 males and 119 females) and 215 were guidance school (91 males and 124 females) students. Mean knowledge score was 17.47 (score range: 0-30) which corresponds to intermediate grade. Mean attitude score was 37 (score range: 13-52) which corresponds to the intermediate grade. Finally and corresponding to a weak grade, their mean practice score was 1.8 (score range: 0-6). Attitude and knowledge showed statistically significant correlation with gender with higher scores in female students. Specific knowledge about leishmaniasis symptoms, carriers and reservoirs were higher than the knowledge about preventive methods. Our results showed that 47.2% of students believed in “fortune” in getting the infection. Although 97.9% of students knew that sand-fly is the carrier, only 28.6% knew what exactly the sand-fly is. Conclusion: Increasing knowledge by giving direct and face to face training to students (the high risk community), teachers and mothers who have a significant role in changing the behavior of the youth is essential. In conclusion, improved knowledge will result in the promotion of the attitude level and especially the behavior of the students to prevent leishmaniasis.